Pneumatic Formwork Systems in Structural Engineering - Benjamin Kromoser; Patrick Huber (Advances in Materials Science and Engineering)
Concrete as a construction material is characterized by high compressive strength, low tensile strength, and good casting ability. In order to fully utilize the potential of this material, the form of load-carrying structures has to be designed according to the stress distribution in the structure. Partially hollow structures, such as hollow beams, or doubly curved structures, such as shells, have favorable characteristics. In hollow structures, material savings are achieved in the individual building components by locally reducing dimensions. Concrete shells, if designed properly, are able to span over large areas by transferring the loads mainly by membrane stresses. The main problem with these structures, however, is the high effort required for producing the complicated formwork. One possibility of reducing this effort is to use a pneumatic formwork. This paper describes different pneumatic formwork systems invented in the past 100 years and presents the latest developments in this area. The many types of possible applications are divided into three categories in order to obtain a clearer overview. Finally, a new construction method, called “Pneumatic Forming of Hardened Concrete (PFHC),” is presented. This method was invented at the TU Vienna and uses the pneumatic formwork in a novel way.